A case of alpha‐fetoprotein‐producing esophageal adenocarcinoma. Issue 2 (22nd October 2012) - Chen, Yi‐Yu; Hsu, Wen‐Hung; Hu, Huang‐Ming; Wu, Deng‐Chyang; Lin, Wen‐Yi
Abstract: Alpha‐fetoprotein is a well‐known tumor marker in the screening and follow‐up of hepatocellular carcinoma. In Taiwanese society, a high prevalence of hepatitis and hepatoma and elevation of alpha‐fetoprotein associated with liver function impairment usually suggested clinics undertake further examination for liver or genital tumor. We report the case of 45‐year‐old man who was found to have an alpha‐fetoprotein‐producing esophageal adenocarcinoma with an initial presentation of liver function impairment and rapid elevation of alpha‐fetoprotein. Esophageal cancer was diagnosed via endoscope and a biopsy proved the presence of adenocarcinoma. A small endoscopic biopsy specimen failed to identify the alpha‐fetoprotein positive tumor cell. Esophagectomy was performed and histopathological study of surgical specimen revealed grade II adenocarcinoma with regional metastatic lymphadenopathy. Immunohistochemical study was focal positive for alpha‐fetoprotein. Serum alpha‐fetoprotein declined transiently after esophagectomy and fluctuation of alpha‐fetoprotein level was noted during the treatment with adjuvant chemotherapy. Finally, 19 months after the operation, the patient died due to multiple organ metastases with multiple organ failure. Thus, a small specimen for upper endoscopy may not be sufficient in the presence of alpha‐fetoprotein‐producing adenocarcinoma. Monitoring of serum alpha‐fetoprotein may be useful in the evaluation and follow‐up of esophageal alpha‐fetoprotein‐producing adenocarcinoma.